Floristic Studies on the Northeast Langkawi - Wati Haron, Noorma; Mohd Zakaria, Rozainah (Malaysian Journal of Science, 2005)
Floristic survey was carried out on some localities in the Northeast of Langkawi. From these localities 69 specimens were collected; 33 were identified to the generic or specific level while 36 were identified to the family level. The distribution of species was discussed and the richness of the limestone and mangrove flora of Langkawi Island warrants the forests to be conserved.